2018
DOI: 10.24191/mar.v17i1.757
|View full text |Cite
|
Sign up to set email alerts
|

Developing Accountability Disclosure Index for Malaysian State Islamic Religious Councils (Sircs): Quantity and Quality

Abstract: This study aims to develop Accountability Disclosure Index (ADI) for Malaysian State Islamic Religious Councils (SIRC), concerning both quantity and quality. In this case, the quality of disclosure items was developed based on the qualitative characteristics, which rely on the International Financial Reporting Standards (IFRS) conceptual framework; namely, relevance, faithful representation, understandability, comparability and timeliness. Each characteristic is scored based on the ‘benchmark’ score, ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…The present study views a comprehensive annual report as a means for the discharge of accountability, supporting many previous studies (For e.g. Masruki et al, 2018;Ntim et al, 2016;Coy et al, 2001) SIRC are constitutionally under the Ruler's jurisdiction in the state administration as a result of colonialism period in . The Ruler shall seek advice from the SIRC.…”
Section: Introductionsupporting
confidence: 87%
“…The present study views a comprehensive annual report as a means for the discharge of accountability, supporting many previous studies (For e.g. Masruki et al, 2018;Ntim et al, 2016;Coy et al, 2001) SIRC are constitutionally under the Ruler's jurisdiction in the state administration as a result of colonialism period in . The Ruler shall seek advice from the SIRC.…”
Section: Introductionsupporting
confidence: 87%
“…However, Shariah control functions, namely Shariah Risk, Shariah Audit, Transparency and Disclosure and Shariah Review seemed to be reported less, which may contribute to Shariah accountability issues (Besar et al 2009). For that reason, this study highlights the importance of implementing quality disclosure and reporting to better discharge accountability of the reporting entity (Masruki et al 2018b). This analysis was further extended to differentiate the Shariah governance practices between local and foreign IBs in Malaysia.…”
Section: Data Analysis and Resultsmentioning
confidence: 95%
“…The results suggested that UK reports' overall quality is better than US 10-K reports, on average. Later, the QCs-based approaches developed by Beest et al (2009) and Braam and Beest (2013) were used by scholars (Agyei-Mensah, 2013;Chakroun and Hussainey, 2014;Dimi et al, 2014;Haarburger et al, 2020;Jerry and Saidu, 2018;Masruki et al, 2018;Mbobo and Ekpo, 2016; The usefulness of IFRScompliant reports Rashid, 2020;Tasios and Bekiaris, 2012) to assess the quality of information set in different contexts, such as financial reporting, corporate governance, and stock market research. Beest and Braams' seminal work on the quality measurement of annual reports allows for crosssectionally and longitudinally comparisons.…”
Section: Qcs Financial Reporting Quality and Ifrs Adoption In Sri Lankamentioning
confidence: 99%